Architectural Design of Online New Student Registration System Using Zachman Framework (Case Study: Gajayana University Malang) - Muhammad Hidayatullah; Achmad Arif Hidayat (International Journal of Multidisciplinary Applied and Science Research, 2025)
The online new student registration system is a platform designed to facilitate the registration process of prospective students efficiently and integratedly, without requiring direct attendance. This study aims to design an online new student registration system for Universitas Gajayana Malang (UNIGA) using the Zachman framework. The main data was obtained from the Education platform, interviews with stakeholders, and a literature review related to the new student registration system. The results of this study include a model of the UNIGA new student registration system involving various processes, such as online registration, prospective student selection, academic management. The implications of this study are to provide a comprehensive overview of the structure of the UNIGA registration system and to design appropriate technological solutions to improve operational efficiency, increase transparency, and accelerate the registration process, which will ultimately improve the experience of prospective students and the operational efficiency of Universitas Gajayana Malang.